Linguistic-stylistic and literary interpretation of S. Zweig's short story "Governess" at the plot and character level - Inna B. Akinshina; Svetlana V. Sleptsova; Oxana V. Kuzmina (Publishing house "Sreda", 2023)
The interaction of literary and linguistic approaches in the process of analyzing a literary text makes it possible to penetrate into the depth of the artistic work. This is the relevance of the study. The authors conducted a philological analysis of the ethical S. Zweig's short story "The Governess" using these approaches. The following means were identified to characterize the psychological tension of the characters: climax and introspection. The analysis of linguistic-stylistic means in the description of the presented images of characters and their interactions is carried out. The analysis revealed the following tropes: direct nominations amplified by the epithets; repetitions of verbs and nouns; artistic comparisons; metaphors; metonymies; paraphrases; hyperboles; personifications; internal parallelisms; figures of "default"; internal monologues; rhetorical questions and exclamations. Three stages of dynamization of the emotional experiences of the main characters are identified with the help of linguistic-stylistic means: 1) slight suspicion, vague contradiction, caution; 2) distrust, suspicion, nervousness, agitation; 3) open protest, experience, grief, despair, disappointment, tears, silence, darkness. The conclusion states that S. Zweig made the best presentation of linguistic and stylistic means to characterize the main characters and the growth of their emotional tension.